PENYULUHAN PENYAKIT CHIKUNGUNYA DI SMA NEGERI 5 PEKANBARU - Bobi Handoko; Abdul Zaky; Sherly Mutiara (LPPM Universitas Awal Bros, 2024)
Chikungunya is a disease caused by the Chikungunya virus (CHIKV) which is characterized by symptoms of high fever and very severe joint pain. The first Chikungunya case that occurred in Indonesia was in Samarinda City in 1973 and was recorded as an Extraordinary Event (KLB), then the case disappeared for approximately 20 years after which it began to appear again in 2001 in Sumatra where it was also recorded as an Extraordinary Event. (KLB). Recorded Chikungunya cases in 2001-2003 reached 3,918 total cases without deaths. This counseling aims to find out how high the death rate is caused by the Chikungunya virus (CHIKV) and find out how to prevent and treat the Chikungunya virus. The method used is outreach which is expected to increase public knowledge regarding Chikungunya disease such as symptoms, prevention and treatment methods.